The Effect of Fixed Asset Intensity and Sales Growth on Tax Avoidance With Leverage as a Moderating Variable Manufacturing - Lutfiah Azzahrah Ulfiqah; Asriani Junaid; Nurfadila (www.amertainstitute.com, 2025)
The purpose of this study was to analyze the effect of fixed asset intensity and sales growth on tax avoidance with leverage as a moderating variable in The manufacturing companies listed on the IDX for the 2021-2023 period. population used in the study were all industrial goods sub-sector companies. The sample in this study used purposive sampling technique involving 12 companies with certain criteria. The research data collection technique uses secondary data. Data analysis in the study used a quantitative approach with the analysis techniques used were descriptive statistical analysis, f test, t test, and Moderated Regression Analysis (MRA). The data in this study were processed and analyzed using the SPSS 30 statistical program. The results of data analysis of this study indicate that: partially fixed asset intensity and sales growth have an effect but not significant on tax avoidance, while leverage moderation on the relationship between fixed asset intensity on tax avoidance and leverage moderation on the relationship between sales growth on tax avoidance has a significant effect. Simultaneously, fixed asset intensity and sales growth variables simultaneously or together affect tax avoidance with leverage as moderation.